A Critical Analysis of the Implementation of Children’s Rights in Kenya - Koech, Peter K.; Njeru, Wilfred K. (Educational Research International, 2014)
This paper analysis the role of stakeholders in implementing children rights in Kenya. The writers looks at the implementation of children rights after the adoption of the New Convection on the Rights of the child by the United Nations General Assembly on 20th November 1989 which, came into force on 2nd September 1990. The convection was created to address the issue of universal rights of the children. The convention has received an overwhelming international response with the exception of the United States and Somalia. The importance of the Convection lies in its status as an international legal and binding instrument. The articles of the Convection stipulate what states an obliged to do in different conditions. The Convection covers civil, political, economic, social and cultural rights. Apart from basic survival requirements such as food, clean water and health care, it also includes rights of protection against abuse, neglect and exploitation and the right to education and participation in social, religious, political and economic activities. The convection represents a turning point in the international movement on behalf of children’s right. In this article, we set out to review the role played by stakeholders in implementing the children’s rights in Kenya. Its worth noting that the government of Kenya has demonstrated its commitment towards children rights in Kenya. However, there are challenges facing implementation process in Kenya. Stakeholders therefore, need to work extra hard on enforcement of Laws affecting children in Kenya
Keywords: Accountability; Child’s Rights; Implementation; Kenya